(untitled) (Research in Agriculture Livestock and Fisheries, 2018)
Bangladesh is predominantly an agricultural country. Agriculture provides employment to nearly about 47.33 percent of its total labor forces (BER, 2015). Broad agriculture sector which includes crops, livestock, fisheries and forestry contributes 16 percent to the Gross Domestic Product (GDP) as a whole in the FY 2013-14 (BER, 2016). Mymensingh district was selected for the study to calculate the profitability and to assess the resource use efficiency of Boro rice production. Simple random sampling technique had been used for collecting data from 60 sample farmers through interview schedule. Both descriptive studies and functional analysis was done to achieve the objectives of the study. The findings of the study revealed that per hectare gross return, net return, and gross margin were found to be BTD110680.00, BTD 25208.94 and BTD 48158.95, respectively. Total costs of rice production were calculated at BTD 85471.06 per hectare. Benefit Cost Ratio (BCR) was found to be 1.29 for Boro rice production. Thus it was found that Boro rice production was profitable. Production function analysis suggested that, among the variables included in the model, quantity of seed, animal labor and power tiller cost, No. of human labor, quantity of fertilizer, cost of irrigation, had a positive and significant effect on the gross yield of Boro rice production, except for cost of manure and cost of pesticides had an insignificant effect on the gross yield of rice production. Efficiency analysis indicated that most of the farmers inefficiently used their inputs. This study also identified some problems associated with Boro rice production. Problems faced by the farmers were ranked on the basis of corresponding percentages. This study provides appropriate suggestion and policy recommendations which will help the development agencies and policy makers of the country for improving the livelihood of the people in the study area. Res. Agric., Livest. Fish.5(3): 293-300, December 2018